ROLE OF DIGITAL TOOLS IN IMPROVING THE EFFECTIVENESS OF LAND MANAGEMENT BY TERRITORIAL СOMMUNITIES - Smoliarchuk , М.; Kovalyshyn , О. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The article examines the evolution of land lease relations in Ukraine, focusing on procedural aspects and the mechanisms of digital transformation that have been implemented with state support. It highlights the features of information support provided by the electronic system Prozorro. Sale, noting its positive impact on establishing objective sale prices, enhancing the investment attractiveness of the land market, and increasing revenues for the local budgets of territorial communities. The study presents analytical data on the sale of municipal land lease rights in Lviv region and analyzes the process of obtaining digital data on land plots from the State Land Cadastre and the registry of real property rights, including any encumbrances. Key trends, challenges, and future prospects for implementing digital technologies are identified. The role of the electronic system Trembita in the development of land relations, particularly concerning the circulation of land lease rights, is emphasized. The article underscores the importance of integrating this system into land lease practices, as it offers numerous benefits, including: reducing document processing times; minimizing administrative barriers by decreasing personal interactions among lessees, lessors, and officials; improving data reliability; optimizing the functions of local self-government bodies by providing rapid access to information about land plots, owners, or lessees within territorial communities; and facilitating integration with electronic auction systems (Prozorro. Sale), thereby ensuring greater transparency and efficiency in land transactions. The integration of open electronic platforms with state registries is shown to create a unified digital environment for managing land resources within territorial communities. The study argues that the digitalization of land lease relations boosts investment activity, enhances managerial decision-making, and fosters trust among participants in the land market. Finally, the paper proposes directions for further development of digital infrastructure, particularly through deeper interoperability of cadastral data with the Trembita system and the expansion of analytical services for local communities.